Consequences of Educational Decentralization in Nepal (Tribhuvan University Journal, 2017)
This study appraises consequences of educational decentralization process (EDP). This Study has Applied qualitative research approach in which information was collected from purposively selected participants belong to 50 primary and secondary schools of 12 districts. This study reveals that in the course of ensuring quality education to all, Nepalese education system implemented EDP. School management committee (SMC) was a sole authority while implementing 'market system' of educational management. Government of Nepal (GoN) had been practicing and delegated authority of school-teacher management to the SMC. Fundamentalism of politics while re-forming SMCs, low academic qualification, lack of managerial skill or capacity of the members had been regarded as some of the mounting challenges. Further, local people including parents were less aware and less capable of assisting SMCs. The policy of handing over SMC had led to increased interest in and ownership of schools by the community in one hand. On the other hand, the education for all (EFA) documents did not focus on empowering the local communities and SMCs for better management of schools in the local level. The large scale program like the Basic and Primary Education Program (BPEP) had in the past concentrated more on capacity building at the central level. No doubt, EDP had been suffering from covertly tight fiscal management policies. Head teachers did not have the rights and responsibility even for recruitment and professional development of the teachers. Poor institutional capabilities, over politicization, nepotism, favoritism had been increasing teacher absenteeism and over-under staffing.